The Woman Burden of HIV/AIDS Patient in Gender Perspective - Awatiful Azza (Universitas Airlangga, 2010)
Introduction:Epidemic HIV/AIDS becomes heavy burden in every country without exception and hardly potency breaks the economic development in developing countries including Indonesia.Method: The method which use on this research was descriptive quantitative. This condition causes women who generally not guilty exactly very susceptible in infection by HIV/AIDS and accounts a real heavy burden from disease impact received by it either in social environment and also family.Result: most all the psychological experienced of respondents change from lightest storey to heaviest. Lack of ability was caused by a lot public still have not comprehended about HIV/AIDS and more tends to discriminates patient and even asks patient to move. Giving of emotion support, psychological, facility, treatment and curative and information support, it's expressed that most of public was less in giving support.Discussion: The effort that is must be done by local government Kabupaten Jember relates to handling of HIV/AIDS for example prevention and invention of case and manage of patient which has expressed positive of HIV/AIDS by entangling all society not to restrain from they environment.The Woman Burden of HIV/AIDS Patient in Gender Perspective